Smoking and Blindness What Optometrists Want their Patients to See - Spafford, Marlee M; Kennedy, Ryan D; Iley, Matthew D; Schultz, Annette S.H. (Canadian Journal of Optometry, 2011)
Most smokers are not aware that their tobacco use is a preventable cause of blindness. Despite the important role optometrists can have impacting patient health choices; their voice has been largely silent in the development of tobacco cessation practice guidelines and health promotion strategies. In this study, we use the International Tobacco Control Policy Evaluation Project (ITC) Four Country Survey to describe the level of Canadian smokers’ knowledge of the association of smoking with blindness and we use focus groups to elicit ideas from Canadian optometrists and senior optometry students about blindness-related graphic warning labels.